Development of Digital Education Comics on Style Around Us to Improve IPAS Learning Outcomes - Rahman, Khoirunnisa Aulia; Andriani, Aldina Eka (FKIP - Universitas Riau, 2025)
This study aims to describe the development design, test the feasibility and effectiveness of Digital Education Comics to improve the learning outcomes of fourth-grade students at SDN Sadeng 03 Elementary School in Semarang City. The type of research used is Research & Development (R&D) with the Borg and Gall development model. The development design of the Digital Education Comic includes components such as the cover, preface, table of contents, learning outcomes, learning objectives, character introduction, reading instructions, content material, bibliography, and developer profile. The feasibility of the Digital Education Comic was assessed by subject matter experts (93.75%), media experts (90.63%), teacher responses (93.75%), and student responses (100%) with the criterion of highly feasible. The effectiveness of the Digital Education Comic is demonstrated by an increase in pretest and posttest results of 23.50%, the results of the paired sample t-test with a sig. value (2-tailed) < 0.001, indicating a significant difference, and the N-Gain test results of 0.663 with a moderate criterion. The conclusion of this study indicates that the Digital Education Comic has been successfully developed, is feasible, and effective in improving the learning outcomes of fourth-grade students at SDN Sadeng 03 Elementary School in Semarang on the topic of forces around us.